At War with Metaphor: Media, Propaganda, and Racism in the War on Terror - Steuter, Erin; Wills, Deborah (Lexington Books, 2009)
When photographs documenting the torture and humiliation of prisoners at Abu Ghraib came to the attention of a horrified public, national and international voices were raised in shock, asking how this happened. At War with Metaphor offers an answer, arguing that the abuses of Abu Ghraib were part of a systemic continuum of dehumanization. This continuum has its roots in our public discussions of the war on terror and the metaphors through which they are repeatedly framed. Arguing earnestly and incisively that these metaphors, if left unexamined, bind us into a cycle of violence that will only be intensified by a responsive violence of metaphor, Steuter and Wills examine compelling examples of the images of animal, insect, and disease that inform, shape, and limit our understanding of the war on terror. Tying these images to historical and contemporary uses of propaganda through a readable, accessible analysis of media filters, At War with Metaphor vividly explores how news media, including political cartoons and talk radio, are enmeshed in these damaging, dehumanizing metaphors. Analyzing media through the lenses of race and Orientalism, it invites us to hold our media and ourselves accountable for the choices we make in talking war and making enemies.